An in-situ setup for simultaneous electro-chemo-mechanical characterization of electrode materials for lithium-ion battery. (15th January 2022) - Chen, Hai-Na; Li, Na; Yang, Le; Liu, Bin; Song, Wei-Li; Chen, Hao-Sen
Abstract: The electro-chemo-mechanical (ECM) coupling effects are nontrivial in alloying electrode materials, whose applications are hindered by the severe volume change during cycling. However, due to the difficulty in the in-situ application of mechanical load onto the active materials, these effects in many emerging lithium-ion battery (LIB) chemistries are largely unknown. Herein, we report a new setup for the in-situ characterizing ECM coupling effects in alloying electrode materials, and the coupling effects in aluminum (Al) foil electrode is studied. The elastic moduli of the Al foil show an increasing then slightly decreasing trend with the lithiation. Meanwhile, electrochemical impedance spectroscopy spectra of the Al foil imply an increasing surface atomistic energetic heterogeneity of the Al foil with the growing tensile force. Furthermore, the stress relaxation phenomena of the Al foil electrode during lithiation are observed. The newly developed setup opens a valuable window into investigating complicated ECM coupling effects in LIBs. Graphical abstract: Image, graphical abstract